Sectoral Restructuring and Labor Mobility: A Comparative Look at the Czech Republic - Vit Sorm; Katherine Terrell (Institute for the Study of Labor (IZA), 2000)
Labor mobility is crucial for an efficient allocation of resources and the transition economies are often viewed as suffering from inadequate reallocation of labor. Using quarterly micro data for the 1994-1998 period, we provide a comparative analysis of the extent and determinants of labor mobility in the Czech Republic. We show there has been significant movement into the finance, trade, and tourism sectors and out of the agricultural and industrial sectors. Over half of the people who change jobs have changed sector of employment, and this restructuring has been carried out relatively efficiently in that it occurred with lower incidence and duration of unemployment than in the other transition economies. The demographic characteristics of different patterns of mobility are similar across these transition economies: we identify younger people in general and single men as individuals who more likely to change jobs or become unemployed. The more educated are experiencing more job stability and are more likely to be hired if unemployed or out of the labor force. Finally, we find in the Czech Republic, the flows between employment and unemployment are very responsive to demand conditions. Hence, we conclude that the Czech labor market is demonstrating flexibility and efficiency in the transition.
Keywords: J23; H53; C41; 330; Labor mobility; sectoral restructuring; Czech Republic; Transition; Central &Eastern Europe; Arbeitsmobilität; Strukturwandel; Arbeitsmarkt; Übergangswirtschaft; Tschechische Republik